Digital technologies and data-driven delay management process for construction projects - Radman, Kambiz; Jelodar, Mostafa Babaeian; Lovreglio, Ruggiero; Ghazizadeh, Eghbal; Wilkinson, Suzanne (Frontiers in Built Environment, 2022)
One of the main challenges of construction projects is managing delays; there is still a lot to overcome to reach near-zero delay (mitigation of delays) in all construction projects. As technology and different platforms are applied to support high volume of data flow acquired from multiple resources during the construction project life cycle; how can these automated and digital progress tracking systems be considered for more effective construction delay management? The aim is to investigate the current state of real-time technologies and their applications and assess how specific attributes of these disruptive technologies can significantly alter delay management in construction industries. Therefore, this study presents a new process-based framework for using technologies with a data lifecycle viewpoint. This research uses a four-step systematic literature review which involves, identification, screening, extortion-eligibility check, and finally selection-inclusion. This is then followed up by thematic content analysis on using new technologies to mitigate delays in construction projects. Key trends, themes, areas of concern for research, and limitations identified in previous literature as research gaps and future needs were documented and structure. This work presents a novel process of comprehensive classification of real-time technologies that are being used in the construction industry to acquire data, screen/analyses data, and present information through an Industry 4.0 application: IoT technologies such as sensors, RFID etc., smartphones, planning/scheduling tools (Ms Project, Primavera), and BIM. The developed process-based framework serves as a roadmap for key stakeholders in construction projects. This framework can cover the lack of strategic real-time communication between project knowledge areas and phases for incorporating a dynamic analytical tracking process into construction project delay management and resulting in enhance construction productivity.